Priming the Abscopal Effect Using Multifunctional Smart Radiotherapy Biomaterials Loaded with Immunoadjuvants - Moreau, Michele; Yasmin-Karim, Sayeda; Kunjachan, Sijumon; Sinha, Neeharika; Gremse, Felix; Kumar, Rajiv; Chow, Kwok Fan; Ngwa, Wilfred (Frontiers in Oncology, 2018)
In this study, we investigate the use of multifunctional smart radiotherapy biomaterials (SRBs) loaded with immunoadjuvants for boosting the abscopal effect of local radiotherapy (RT). SRBs were designed similar to currently used inert radiotherapy biomaterials, incorporating a biodegradable polymer with reservoir for loading payloads of the immunoadjuvant anti-CD40 monoclonal antibody. Lung (LLC1) tumors were generated both on the right and left flank of each mouse, with the left tumor representing metastasis. The mice were randomized and divided into 8 cohorts with 4 cohorts receiving image-guided radiotherapy (IGRT) at 5 Gy and another similar 4 cohorts at 0 Gy. IGRT and Computed Tomography (CT) imaging were performed using a small animal radiation research platform (SARRP). Tumor volume measurements for both flank tumors and animal survival was assessed over 25 weeks. Tumor volume measurements showed significantly enhanced inhibition in growth for the right flank tumors of mice in the cohort treated with SRBs loaded with CD40 mAbs and IGRT. Results also suggest that the use of polymeric SRBs with CD40 mAbs without RT could generate an immune response, consistent with previous studies showing such response when using anti-CD40. Overall, 60% of mice treated with SRBs showed complete tumor regression during the observation period, compared to 10% for cohorts administered with anti-CD40 mAbs but no SRB. Complete tumor regression was not observed in any other cohorts. The findings justify more studies varying RT doses and quantifying the immune-cell populations involved when using SRBs. Such SRBs could be developed to replace currently used radiotherapy biomaterials, allowing not only for geometric accuracy during RT but also for extending RT to the treatment of metastatic lesions.